1987
DOI: 10.1002/actp.1987.010380102
|View full text |Cite
|
Sign up to set email alerts
|

Zur kinetik der Polykondensation von Terephthalsäure und Ethylenglykol in dünnen Schmelzeschichten

Abstract: Auf der Grundlage eines mehrparametrigen Reaktions‐Stofftransport‐Modells wurden die Geschwindigkeitskonstanten der wichtigsten chemischen Reaktionen und die Transportkoeffizienten von Ethylenglykol und Wasser bei der Polykondensation carboxylgruppenhaltiger Oligo(ethylenterephthalat)‐Schmelzen crmittelt. Der Parameteridentifizierung wurden Polykondensationsversuche in dünnen Schmelzeschichten zugrundegelegt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…In Figure 2.27, the good quality experimental data of Rafler et al [106] for the antimony acetate catalyzed polycondensation under vacuum are shown, demonstrating the dependency of the overall polycondensation rate on the polymer film thickness.…”
Section: Diffusion and Mass Transfer In Melt-phase Polycondensationmentioning
confidence: 75%
See 2 more Smart Citations
“…In Figure 2.27, the good quality experimental data of Rafler et al [106] for the antimony acetate catalyzed polycondensation under vacuum are shown, demonstrating the dependency of the overall polycondensation rate on the polymer film thickness.…”
Section: Diffusion and Mass Transfer In Melt-phase Polycondensationmentioning
confidence: 75%
“…Currently, the accepted interpretation of experimental evidence is that the polycondensation of PET in industrial reactors is dominantly controlled by diffusion of EG in the melt phase [1,6,8,[102][103][104][105][106][107][108][109][110].…”
Section: Diffusion and Mass Transfer In Melt-phase Polycondensationmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of the mass transfer rate constants for the volatile species such as EG, free DEG, and water were set to 0.05 s Ϫ1 . 2,10,12 The reactions in Table IV were taken into consideration in this study. The vapor-liquid equilibrium compositions were computed with the Flory-Huggins model.…”
Section: Table IV Reactions Considered In the Prepolymerization And Pmentioning
confidence: 99%
“…The forward reaction of polycondensation is accelerated if the pressure is kept low, and this brings about a much more effective removal of EG. The values of the mass transfer rate constants for the volatile species such as EG, free DEG, and water were set to 0.05 s −1 2, 10, 12. The reactions in Table IV were taken into consideration in this study.…”
Section: Introductionmentioning
confidence: 99%